A Retrospective Evaluation of the Clinical Outcome of Dental Implants Following Maxillary Sinus Augmentation with and without Bone Grafting - Asna Khalid, Sufyan Ahmed, Syed Muhammad Zaki Mehdi, Ayesha Ilyas, Aimen, Tariq Sardar (Pakistan Journal of Medical & Health Sciences, 2023)
The reintegration of partial edentulism patients is the utmost common treatment performed by dental practitioners in relations of frequency & occurrence, even though the general decline in tooth loss seen in recent times. There is broad agreement among dental professionals that osseointegrated implant-supported prostheses are the preferred method for replacing an edentulous gap caused by one or more lost teeth. These implants have been shown to provide several benefits for both physical and mental health. Objectives: The current retrospective study sought to define and assess the 60 months follow-up of implants inserted in patients who needed sinus floor elevation surgery in the maxillary arch. Following a single-stage surgical method with delayed implant insertion, the impact of various RABH & the usage of graft and graft less methods were evaluated. Methodology: Patients chosen for the current retrospective study were selected from the data-based logbooks kept by the oral surgery department between January 2017 and December 2022. All patients who had concomitant lateral sinus floor elevation & implant insertion from the same department were evaluated in the current study after obtaining formal approval from the IRB of the institute. Results: 86 grafted sinuses received a sum of 239 implants, each assessing 10 & 12 millimeters in length and 4 or 5 mm in breadth. Specific measurements revealed that the majority were 4 mm broad & 10 mm long. Using a manual torque wrench, it was determined that all implants, regardless of size, attained an insertion torque of >35 Ncm at the moment of implantation. In 41 patients, xenograft was employed, corresponding to 60 sinuses; in contrast, in 45 patients, graft-less surgery was performed, corresponding to 62 sinuses. An average follow-up of 43 months was used. Conclusion: Maxillary sinuses with a RABH of more than four millimeters can be effectively transplanted using a single-stage xenograft technique. One-stage graft-less surgeries with blood clot alone & swift implant implantation should only be used in sinuses with a RABH > 6 mm since they have lower success rates. Practical Implication: The following study will help oral surgeon in choosing the surgery carried out for the implant placement involving the sinuses. Keywords: Dental Implants, Bone Replacements, Sinus Augmentation, Grafting Materials